2016
DOI: 10.3389/fenvs.2016.00015
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Diversity of Soil Mite Functional Groups Respond to Extensification of Land Management, Potentially Affecting Soil Ecosystem Services

Abstract: Soil mites (Acari) are ubiquitous in soil ecosystems and show a vast taxonomic diversity with a wide range of life history characteristics and feeding strategies. Various taxa contribute directly or indirectly to soil processes, including nutrient cycling, soil formation and pest control. Mites thus support important ecosystem services of soils. Yet, their community composition, and therewith service provisioning, may differ between for instance intensively managed agricultural soils and extensively managed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 58 publications
4
10
0
Order By: Relevance
“…In contrast, grasslands with less extensive management practices, and more diverse plant communities, which provide an environment with more habitats and more accessible food sources, can maintain higher densities of soil organisms (Alvarez et al, 2001; Nyawira Muchane, 2012; Scherber et al, 2010). Accordingly, we found significantly higher levels of microarthropod biomass in grasslands than in croplands, which is supported by previous studies (e.g., de Groot et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, grasslands with less extensive management practices, and more diverse plant communities, which provide an environment with more habitats and more accessible food sources, can maintain higher densities of soil organisms (Alvarez et al, 2001; Nyawira Muchane, 2012; Scherber et al, 2010). Accordingly, we found significantly higher levels of microarthropod biomass in grasslands than in croplands, which is supported by previous studies (e.g., de Groot et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Compared with croplands, grasslands (with less intensive disturbance but more diverse plant communities) provide an environment with more habitats and more accessible food sources, can maintain higher densities of soil organisms ( Alvarez et al, 2001 ; Nyawira Muchane, 2012 ; Scherber et al, 2010 ). Accordingly, we found significantly higher levels of microarthropod density and biomass in grasslands than in croplands, which is supported by previous studies (e.g., de Groot et al, 2016 ). Similarly, microarthropod density and biomass are expected to be also reduced by the intensified management practices, e.g., monoculture, heavy use of mineral fertilizers and pesticides in croplands, and frequent fertilization, mowing, and grazing in grasslands; however, we did not find any evidence for this in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In Europe, these species have been identified mostly in grasslands, grassy arable fallows or urban habitats, their communities being correlated with soil moisture ( Onchodellus karawaiewi being a euryhygrophilous species) or organic matter content. In our study, this explains the relationship between such mites and RP 20 , 25 , 44 , 60 , 79 .…”
Section: Discussionsupporting
confidence: 63%
“…Research studies from all over the world revealed that the Mesostigmata communities correlated with environmental variables could constitute a very useful biological tool to characterized the ecological quality of terrestrial ecosystems and the quality of soils 9,10,18,21,[25][26][27][29][30][31]33 . In the case of urban green areas from Bucharest, under different management scenarios, their ecological characterization was made taking into account the variation of the environmental parameters, in correlation with spatial dynamics of the communities' parameters of Mesostigmata fauna (species diversity and numerical abundance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation